Using of Monofocal Intraocular Lenses Different Types for Cataract Surgery in Adult Patients: Systematic Review - I. S. Krysanov; V. S. Krysanova; V. Yu. Ermakova (Oftalʹmologiâ)
Objectives: to perfom analysis of the clinical efficacy and safety of using monofocal IOLs in the surgical treatment of cataracts in adult patients. Material and methods. In available sources (databases of the Cochrane Library and Medline) a search was conducted to evaluate the effectiveness and safety of using monofocal IOLs in cataract surgery in adult patients according to the PICO(S) regimen. A literature review was conducted in July 2018 for the keywords “intraocular lenses” and “cataract” using the following filters: clinical trial, randomized clinical trial, meta-analysis, systematic review (clinical trial, randomized clinical trial, meta-analysis, systematic review). Posting languages: English. Depth of search — 5 years. Last search date is July 27, 2018. Results. An initial search in the Medline database found 21,737 publications and 2157 in the Cochrane Library database. A total of 17,894 links were found. In a meta-analysis Zhao Y. et al., 2017, a comparison of the incidence of opacities of the posterior capsule (secondary cataract) after surgical treatment with the implantation of hydrophobic and hydrophilic IOLs was made. In multicenter retrospective cohort study Ursell P., et al, 2018 assessed the frequency of the Nd: YAG-laser capsulotomy for the treatment of secondary cataract which developed after the implantation of the IOL within the first 3 years after surgery. Conclusion. During the systematic review, the relationship between the incidence of complications (secondary cataracts) and the properties of the IOL material was found. The implantation of lenses from a hydrophobic material is associated with a lower incidence of secondary cataracts than the implantation of lenses from a hydrophilic material.